Protective efficacy of anti-neuraminidase monoclonal antibodies against H7N9 influenza virus infection - Fei-Fei Xiong; Xue-Ying Liu; Fei-Xia Gao; Jian Luo; Peng Duan; Wen-Song Tan; Ze Chen (Emerging Microbes and Infections)
The H7N9 influenza virus has been circulating in China for more than six years. The neuraminidase (NA) has gained great concern for the development of antiviral drugs, therapeutic antibodies, and new vaccines. In this study, we screened seven mouse monoclonal antibodies (mAbs) and compared their protective effects against H7N9 influenza virus. The epitope mapping from escape mutants showed that all the seven mAbs could bind to the head region of the N9 NA close to the enzyme activity sites, and four key sites of N9 NA were reported for the first time. The mAbs D3 and 7H2 could simultaneously inhibit the cleavage of the sialic acid of fetuin protein with large molecular weight and NA-XTD with small molecule weight in the NA inhibition experiment, prevent the formation of virus plaque at a low concentration, and effectively protect the mice from the challenge of the lethal dose of H7N9 virus.